A Product Pain-Pleasure Framework for Software Product Design in the Usability and User Experience Domains - Hashim W.; Mkpojiogu E.O.C.; Hussain A.; Abdul-Aziz S.N. (Webology Center, 2023)
This study utilized a literature review strategy to examine prior literature pertaining to the frameworks concerning how to minimize users pain and maximize their pleasure while interacting with the designs of interactive products. The findings of the study reveal that several such frameworks are in existence and are mainly in other domains different from usability and user experience. In these, the emphasis were mostly on satisfaction and dissatisfaction criteria which do not cover the broader perspectives of user experience that comprise hedonic, affective, aesthetics and other hedonomic facets. This prompts for the development of a framework that tailored to usability and user experience concerns to enable user experience designers design interactive products that will enhance users experience. The proposed framework was adapted from previous related frameworks It is a three-factor framework that is composed of pain factors, linear factors and pleasure factors. The study proposes this framework to facilitate the design of interactive systems that improves the experience of users. 2021, Webology. All rights reserved